1988
DOI: 10.1007/bf00221754
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of opsin- and VIP-like-immunoreactivity in CSF-contacting neurons of the avian brain

Abstract: Cerebrospinal fluid-contacting (CSF) cells in both the septal and the tuberal areas in the brain of the ring dove are labeled by RET-P1, a monoclonal antibody to opsin that reacts with inner and outer segment membranes of rod photoreceptors in a variety of vertebrates. Immunoblot analysis of proteins from diverse brain regions, however, revealed bands of anti-RET-P1 immunoreactivity that did not correspond to opsin. Binding of RET-P1 to opsin-containing membranes, was not inhibited by membranes rich in muscari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(133 citation statements)
references
References 31 publications
8
124
1
Order By: Relevance
“…Multiple photoreceptors are likely involved in the photoperiodic response, as has been reported for circadian photoreception, which involves both visual photoreceptors (rod and cones) and nonvisual photoreceptors (melanopsin) (42,43). Although rhodopsin-like immunoreactivity has been observed in the pigeon septal region (11,12), multiple independent studies failed to detect similar signals in the quail brain (13,14). Expression of melanopsin has been demonstrated in the lateral septal region as well as the retina and pineal gland in chicks (15).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Multiple photoreceptors are likely involved in the photoperiodic response, as has been reported for circadian photoreception, which involves both visual photoreceptors (rod and cones) and nonvisual photoreceptors (melanopsin) (42,43). Although rhodopsin-like immunoreactivity has been observed in the pigeon septal region (11,12), multiple independent studies failed to detect similar signals in the quail brain (13,14). Expression of melanopsin has been demonstrated in the lateral septal region as well as the retina and pineal gland in chicks (15).…”
Section: Discussionmentioning
confidence: 86%
“…In 1985, Foster et al and Foster and Follett reported an action spectrum for the photoperiodic responses of quail and suggested the possible involvement of rhodopsin-like photoreceptors (9,10). Indeed, gene expression and immunoreactivity for rhodopsin have been reported in the septal region of the pigeon (11,12). Surprisingly, in several studies, rhodopsin-like immunoreactivity has not been successfully detected in the quail (13,14).…”
mentioning
confidence: 99%
“…Despite the marked differences that exist between the mammalian and avian light input pathways for the regulation of photoperiodism, the MBH is considered the center for photoperiodic time measurement in both mammals and birds. This is because lesions in the MBH block photoinduced LH release (Sharp & Follett 1969, Davies & Follett 1975 even though the GnRH neurons are left intact (Juss 1993) and deep brain photoreceptors are thought to be localized in this region (Silver et al 1988, Saldanha et al 1994. In addition, circadian clock genes are expressed in the MBH, and the circadian clock they regulate appears to be the long-sought biological clock responsible for photoperiodic time measurement (Ball & Balthazart 2003.…”
Section: Melatonin and Seasonalitymentioning
confidence: 99%
“…Although clock genes are expressed rhythmically in the quail SCN and pineal, only in the MBH does the rhythm remain constant under experimental light-dark regimes. The critical role of the MBH in avian photoperiodism is further underscored by the facts that 1) this region probably also contains the deep-brain photoreceptors that are responsible for reproductive photoinduction (Silver et al, 1988;Saldanha et al, 1994bSaldanha et al, , 2001, and 2) the MBH exhibits significant Fos responses to photic cues .…”
Section: The Medial-basal Hypothalamus Brain Deiodinase and Photopermentioning
confidence: 99%